2017
DOI: 10.1038/s41598-017-11790-0
|View full text |Cite
|
Sign up to set email alerts
|

A Phytochemical Approach to Promotion of Self-renewal in Murine Spermatogonial Stem Cell by Using Sedum Sarmentosum Extract

Abstract: Spermatogonial stem cells (SSCs) are the basis of spermatogenesis, which is dependent on the ability to self-renew and differentiation. Controlling self-renewal and differentiation of SSCs could apply to treatment of disease such as male infertility. Recently, in the field of stem cell research, it was demonstrated that effective increase in stem cell activity can be achieved by using growth factors derived from plant extracts. In this study, our aim is to investigate components from natural plant to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…In the case of ROS, current studies identified the bilateral aspects of ROS in spermatogenesis working as activators as well as inhibitors [ 173 ]. Novel mechanisms such as the proliferation of SSC by 5H-purin-6-amine, PI3K/AKR, SFK signaling pathways, and the lack of Nrf2 genes were reported to probably affect arsenic-induced reproductive toxicity [ 41 , 59 ]. Moreover, the fluctuation of hormones such as FSH, are caused by more than one physiological process, therefore the hormonal changes by certain natural products should be interpreted with a wider variety of possibilities [ 174 , 175 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ROS, current studies identified the bilateral aspects of ROS in spermatogenesis working as activators as well as inhibitors [ 173 ]. Novel mechanisms such as the proliferation of SSC by 5H-purin-6-amine, PI3K/AKR, SFK signaling pathways, and the lack of Nrf2 genes were reported to probably affect arsenic-induced reproductive toxicity [ 41 , 59 ]. Moreover, the fluctuation of hormones such as FSH, are caused by more than one physiological process, therefore the hormonal changes by certain natural products should be interpreted with a wider variety of possibilities [ 174 , 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results identified that date palm pollen extract could be clinically used to enable the proliferation and differentiation of sperm cells. Jung et al reported that 5H-purin-6-amine at doses of 0.01, 0.1, 1, and 10 µg/mL originated from Sedum sarmentosum , was an effective compound inducing spermatogonial stem cells proliferation [ 41 ]. Spermatogonial stem cells (SSC) from C57BL/6-TG-EGFP were cultured for 1 week with 1 µg/mL 5H-purin-6-amine which was identified as n-butanol fraction (Bu) of Sedum sarmentosum .…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“… Sertoli cells, spermatogonia stem cells from mice 0.06, 0.25, 0.62 mg/mL; 14 days Increase in proliferation of spermatogonia [84] Plant 5 H-purin-6-amine, Sedum sarmentosum extract In vitro Sedum sarmentosum Spermatogonial stem cells C57BL. 6-TG-EGFP 0.01, 0.1, 1, 10 mg/mL; 1 week Increase of self-renewal in SSCs ↑ PLZF, GFRα1, VASA, Lhx1 ↓ Pgk2 [85] Plant Licorice extract In vitro Glycyrrhiza uralensis Fisch. Testis tissue from C57BL/6 N mice 0.2, 2, 20 µmol/L; 72 h Increase in proliferation of spermatogonia ↑ PCNA, SCP3, Spo11 [86] Plant Lycium barbarum polysaccharide In vitro Lycium barbarum Linn.…”
Section: Antioxidants In the Treatment Of Male Infertilitymentioning
confidence: 99%
“…Metabolit sekunder tumbuhan adalah salah satu agen kimiawi eksogen yang dapat mempengaruhi efisiensi spermatogenesis. Antioksidan atau reactive oxygen species (ROS) inhibitor berperan penting dalam menjaga kesehatan sel-sel spermatogenik sehingga dapat tumbuh dan berkembang dengan baik (Jung et al, 2017;Noh et al, 2020).…”
Section: Pengaruh Pemberian Fblmu Dan Fblma Terhadap Berat Relatif (I...unclassified